2006
DOI: 10.1258/096914106778440572
|View full text |Cite
|
Sign up to set email alerts
|

Interval breast cancers: prognostic features and survival by subtype and time since screening

Abstract: Objectives To investigate the hypothesis that interval cancers arising soon after the previous screen and true interval cancers are biologically aggressive and have a relatively poor prognosis compared with other interval cancers, and to assess which prognostic features are relevant to interval cancers. Methods Analysis of prognostic pathological features (grade, lymph node stage, size, vascular invasion, oestrogen receptor [ER] status and histological type), radiological features (comedo/noncomedo calcificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
4
22
1
Order By: Relevance
“…However, these results are in agreement with the hypothesis of a relationship between HRT and interval cancers, as reported by some authors [18,31]. Metastases to regional lymph nodes were more frequent among interval breast cancers (especially false negative tumors), as observed by other authors [7,8,17,32]. This finding is partly related to the longer time to diagnosis [32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, these results are in agreement with the hypothesis of a relationship between HRT and interval cancers, as reported by some authors [18,31]. Metastases to regional lymph nodes were more frequent among interval breast cancers (especially false negative tumors), as observed by other authors [7,8,17,32]. This finding is partly related to the longer time to diagnosis [32].…”
Section: Discussionsupporting
confidence: 91%
“…Metastases to regional lymph nodes were more frequent among interval breast cancers (especially false negative tumors), as observed by other authors [7,8,17,32]. This finding is partly related to the longer time to diagnosis [32].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…11, 13, 14, 26, 31, 3537, 39, 4348 For the majority of studies, which compared interval BCs with screen-detected cancers, there were consistent findings that interval BCs had worse prognostic features, such as larger tumour size, higher frequency of node metastases, higher histologic grade, and more advanced disease compared to screen-detected BC (Table 3). Although biomarker data were not consistently reported in these studies, where reported there was evidence that interval BCs had a higher frequency of triple-negative or HER2-positive cancers and a lower frequency of hormone receptor-positive cancers than screen-detected BC (Table 3).…”
Section: Resultsmentioning
confidence: 80%
“…These seem to represent a group of more aggressive tumours; therefore, the findings associated with this type of tumour at screening mammography should be followed up with complementary tests. The conclusions of other authors, however, have not always agreed about these possible differences (Ikeda et al, 1992), as Porter et al, 2006 point out in their recent article. Some authors have suggested the hypothesis that tumours diagnosed in the first year after a screening mammogram (earlypresenting IC) could be more aggressive, having greater lymph-node involvement and a worse histological grade than those diagnosed later (Frisell et al, 1992;Fracheboud et al, 1999).…”
Section: Discussionmentioning
confidence: 89%